Evaluation of the potential for diagnosis of fungal keratitis using a Fusarium-specific antibody - Hye-Jeong Jo; Min-Jeong Kim; Hae-Ahm Lee; Fu-Shi Quan; Hyun-Hee Kong; Eun-Kyung Moon (Scientific Reports)
Abstract The increasing number of contact lens users correlates with a rise in the incidence of fungal keratitis. Fungal keratitis can lead to blindness if not treated promptly, and its early symptoms are similar to those of bacterial and amoebic keratitis, making rapid diagnosis challenging. This study aimed to assess the potential of using a peptide antibody against the fungal-specific protein ERG24, which encodes sterol C-14 reductase, to differentiate fungal keratitis from other forms of keratitis. The specificity of the ERG24 antibody was assessed through Western blot and enzyme-linked immunosorbent assay (ELISA). Immunocytochemistry (ICC) was performed by co-culturing two types of fungi, Acanthamoeba, and two bacterial strains with human corneal epithelial (HCE) cells. Additionally, to evaluate the diagnostic potential of the ERG24 antibody, animal models of fungal, amoebic, and bacterial keratitis were developed, and ELISA was conducted on tear and ocular lysates from these models. The results demonstrated that the antibody specifically reacted with Fusarium solani in Western blot, and both ELISA and ICC confirmed that the ERG24 antibody did not react with HCE cells, Acanthamoeba, or bacteria, but was specific to the two fungal species. In vivo experiments further showed that the ERG24 antibody significantly detected F. solani in tear-wash samples and eyeball lysates from the fungal keratitis model, without reacting with samples from amoebic and bacterial keratitis models. This study suggests that the ERG24 peptide antibody could provide valuable information for developing differential diagnostic methods for fungal keratitis compared to other forms of keratitis.